Preaching a dual identity : Huguenot sermons and the shaping of confessional identity, 1629-1685 - Must, Nicholas (St. Andrews studies in Reformation history., 2017)
In Preaching a Dual Identity , Nicholas Must examines seventeenth-century Huguenot sermons to study the development of French Reformed confessional identity under the Edict of Nantes. Of key concern is how a Huguenot hybrid identity was formulated by balancing a strong sense of religious particularism with an enthusiastic political loyalism. Must argues that sermons were an integral part of asserting this unique confessional position in both their preached and printed forms. To demonstrate this, Must explores a variety of sermon themes to access the range of images and arguments that preachers employed to articulate a particular vision of their community as a religious minority in France.